KONSTRUKSI SOSIAL GENDER DALAM REALITAS JABATAN PUNCAK (Studi Tentang Perempuan Pimpinan di Pemerintah Provinsi DIY) - Lukmono Hadi (Jurnal Paradigma, 2017)
The research is aimed at obtaining knowledge and understanding – through social construction perspective – on how woman government officers achieve their political reality, that is to become the top leaders (political leaders) in Yogyakarta (DIY) Province. The research is conducted by using interpretive qualitative (phenomenology) method, while its study subjects are woman government officers who hold top management positions within the government of DIY Province. To complete the research, the analysis is also conducted based on data taken from other informants. The finding of the research shows that the career constructions of the women in this study are possible due to a range of experiences that influence their lives since their childhoods. They are able to achieve the leadership position because throughout their career, they are able to objectify their competence and self-confidence. They are also able to internalize their competence and self-confidence, which then are getting stronger. These strong feeling of competence and self-confidence then make them dare to compete and they are willing to take the risk in pursuing their career up to these top positions. Based on those finding, the research concludes that women of these top positions (public leader) are actually the reality that is constructed socially. The social construction involves three processes, namely externalization, objectification, and internalization.